The title and the rational use of land as aspects of the lawful conduct of subjects of land law - Санніков, Д. В. (Theory and practice of jurisprudence, 2016)
The article is devoted to topical issues of the title of land use, land use management, their relationship . This article analyzes the methods and mechanisms of the state to land relationship in general, as well as the behavior of the subjects of such relationship, suggests ways to improve public policy in ensuring the proper use of land.